2018
DOI: 10.1007/s12094-018-1927-z
|View full text |Cite
|
Sign up to set email alerts
|

TIPE1 suppresses osteosarcoma tumor growth by regulating macrophage infiltration

Abstract: Collectively, our results demonstrate the anti-tumor role of TIPE1 in osteosarcoma and reveal a novel therapy target for osteosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 24 publications
2
17
1
Order By: Relevance
“…TIPE1 also inhibits breast cancer cell proliferation, both in vivo and in vitro ( 27 ), whereas it serves as an oncogene in the pathogenesis of cervical cancer ( 17 ). Furthermore, TIPE1 overexpression effectively inhibits osteosarcoma tumor growth in vivo , which may contribute to the inhibition of macrophage infiltration in osteosarcoma ( 18 ). In the present study, the tumor suppressor role of TIPE1 in ovarian cancer was confirmed by promoting apoptosis in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TIPE1 also inhibits breast cancer cell proliferation, both in vivo and in vitro ( 27 ), whereas it serves as an oncogene in the pathogenesis of cervical cancer ( 17 ). Furthermore, TIPE1 overexpression effectively inhibits osteosarcoma tumor growth in vivo , which may contribute to the inhibition of macrophage infiltration in osteosarcoma ( 18 ). In the present study, the tumor suppressor role of TIPE1 in ovarian cancer was confirmed by promoting apoptosis in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic TIPE1 expression promotes apoptosis and inhibits cell invasion and migration in several types of cancer ( 14 16 ); however, in cervical cancer, TIPE1 facilitates cell proliferation and suppresses the susceptibility of cells to cisplatin chemotherapy ( 17 ). Furthermore, ectopic TIPE1 expression significantly impairs osteosarcoma tumor growth in vivo by inhibiting macrophage infiltration ( 18 ). However, the role of TIPE1 in ovarian serous cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor-associated macrophages (TAMs) serve as crucial modulators of the complicated interactions between tumors and the immune system 8. Treatment approaches that affect the bioactivity and/or existence of macrophages have been proved to be promising preclinically and are currently being assessed clinically 9,10. Stimulated macrophages are able to phagocytose malignant cells by hindering the interaction between CD47 and signal regulatory protein alpha (SIRPa), which has been con-temporarily applied to cancer treatment in various clinical trials 1113.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al showed that TIPE1 can induce hepatocellular carcinoma cells to undergo apoptosis by negatively regulating Rac1 activation (12). Moreover, very recent studies indicated that TIPE1 suppresses tumor growth, invasion, and migration in osteosarcoma, lung cancer, and gastric carcinoma (1315). However, our recent research demonstrated that TIPE1 could promote cervical cancer proliferation, and thus preserves it as a poor prognostic factor for patients with cervical cancer (16), indicating that its biological functions for tumorigenesis remain ambiguous.…”
Section: Introductionmentioning
confidence: 99%